Электромагнитные излучения в выхлопной части паровой турбины - Тарелин, А.А.; Нечаев, А.В.; Хиневич, А.Е. (Проблемы машиностроения, 2017)
В статье представлена информация об электромагнитных излучениях в зоне выхлопа турбины, связанных с электризацией влажного пара. Приведены данные измерений электромагнитного излучения за последней ступенью турбины. Описаны эффекты влияния электромагнитных явлений на экспериментальное электротехническое оборудование, размещенное в конденсаторе турбины. Обсуждаются возможные механизмы влияния электромагнитных излучений на эффективность и надежность турбоустановки Подана інформація про електромагнітні випромінювання в зоні вихлопу турбіни, пов'язані з електризацією вологої пари. Наведені дані вимірів електромагнітного випромінювання за останнім ступенем турбіни. Описані ефекти впливу електромагнітних явищ на експериментальне електротехнічне устаткування, розміщене в конденсаторі турбіни. Обговорюються можливі механізми впливу електромагнітних випромінювань на ефективність і надійність турбоустановки Electrization of working fluid in the wet steam turbine results in occurrence of electromagnetic radiation in the exhaust part of the turbine. The purpose of the investigation is experimental study of parameters electromagnetic radiation and discuss its influence on the efficiency and reliability of turbine. Electromagnetic radiation received by string antennas in the turbine exhaust part. Measurement of electromagnetic radiation parameters was carried out by using a spectrum analyzers. It has been found electromagnetic radiation in the form of noise from kilohertz to tens of megahertz. It was also found high frequency component near 2 GHz. Total power of the electromagnetic radiation of ionized wet steam flow in exhaust part turbine can reach several kilowatts. Proof of this can be found in the experiment damage of cables insulation laid in the turbine condenser. Another manifestation electromagnetic radiation are high frequency current induced in the electric circuit of the probe installed in the exhaust of the turbine. Results presented in the paper show that the electromagnetic radiation can affect on performance and reliability of the wet steam turbine